A descriptive study of the surge response and outcomes of ICU patients with COVID‐19 during first wave in Nordic countries. Issue 1 (3rd October 2021) - Chew, Michelle S.; Kattainen, Salla; Haase, Nicolai; Buanes, Eirik A.; Kristinsdottir, Linda B.; Hofsø, Kristin; Laake, Jon Henrik; Kvåle, Reidar; Hästbacka, Johanna; Reinikainen, Matti; Bendel, Stepani; Varpula, Tero; et al.
Abstract: Background: We sought to provide a description of surge response strategies and characteristics, clinical management and outcomes of patients with severe COVID‐19 in the intensive care unit (ICU) during the first wave of the pandemic in Denmark, Finland, Iceland, Norway and Sweden. Methods: Representatives from the national ICU registries for each of the five countries provided clinical data and a description of the strategies to allocate ICU resources and increase the ICU capacity during the pandemic. All adult patients admitted to the ICU for COVID‐19 disease during the first wave of COVID‐19 were included. The clinical characteristics, ICU management and outcomes of individual countries were described with descriptive statistics. Results: Most countries more than doubled their ICU capacity during the pandemic. For patients positive for SARS‐CoV‐2, the ratio of requiring ICU admission for COVID‐19 varied substantially (1.6%–6.7%). Apart from age (proportion of patients aged 65 years or over between 29% and 62%), baseline characteristics, chronic comorbidity burden and acute presentations of COVID‐19 disease were similar among the five countries. While utilization of invasive mechanical ventilation was high (59%–85%) in all countries, the proportion of patients receiving renal replacement therapy (7%–26%) and various experimental therapies for COVID‐19 disease varied substantially (e.g. use of hydroxychloroquine 0%–85%). Crude ICU mortality ranged from 11% to 33%. Conclusion: There was substantial variability in the critical care response in Nordic ICUs to the first wave of COVID‐19 pandemic, including usage of experimental medications. While ICU mortality was low in all countries, the observed variability warrants further attention.